AKUNTABILITAS DAN TRANSPARANSI PENGELOLAAN DANA DESA DI KECAMATAN TRENGGALEK TAHUN 2017 - Eferyn, Krissantina; Sa’diyah , Halimatus (Universitas Nusantara PGRI Kediri, 2021)
Trenggalek sub-district is one of the sub-districts that receives village funds. In 2017, Trenggalek sub-district received an increase in village funds by 27% from the previous year. reporting system that requires the village government must be accountable and transparent. For this reason, research on the accountability and transparency of village fund management in Trenggalek subdistrict in 2017. This type of research is qualitative research with a descriptive analysis approach. The data used in this study are primary data and also secondary data. The data collection used in this study is as follows interview, observation and documentation. To test the validity of the data obtained, triangulation techniques are used.Based on the results of the study, it was found that the accountability and transparency of village fund management in Trenggalek subdistrict was carried out starting from the planning, implementation and reporting process.Accountability in planning and implementation is done by involving the community or community participation in planning APBDes. The implementation of the activities was carried out with the Swakelola principle carried out by the TPK. In accountability, accountability is carried out in stages by carrying out each activity process starting from planning, implementing and reporting in accordance with the rules that have been established and submitting evidence of the results of the use of village funds. In terms of transparency, planning up to reporting, it is carried out openly by providing information tools in the form of notice boards displayed in front of the village hall or in the location of physical project development.